Facilitators, barriers, and strategies for the implementation of peer-led tuberculosis active case finding among people who use drugs in Dar es Salaam, Tanzania - Lilian Tina Minja; Liana Monica Minja; Kilian Mlalama; Doreen Pamba; Jerry Hella; Samwel Likindikoki; Cassian Nyandindi; Jessie Mbwambo; Klaus Reither; Jennifer M. Belus (PLoS ONE, 2025)
Background Globally, tuberculosis (TB) is the leading cause of death from a single infectious agent. In 2023, an estimated 2.7 million cases of TB were undiagnosed or unreported. To address missing cases, the World Health Organization recommends systematic screening for TB. This is synonymous to active case finding (ACF) and involves provider-initiated screening and testing for TB. Despite the high incidence and prevalence of TB among people who use drugs (PWUD), there is a significant gap in data, on their perspectives, regarding the implementation of TB ACF services. This study aimed to explore facilitators and barriers to implementing peer-led TB ACF, as perceived by both, current and potential service users. Methods We conducted in-depth interviews among purposively selected adult PWUD in Dar-es-Salaam region, Tanzania. Study participants included: (1) peer PWUD with prior history of illicit drug use and medication-assisted treatment (MAT) (n = 10), (2) current medication-assisted treatment service users receiving clinic-based daily methadone (n = 8), and (3) community PWUD not on MAT recruited from various community locations (n = 4). All peer PWUD were experienced in TB ACF. Thematic content analysis was utilized with the support of NVivo12. Results Our findings are presented into two categories: individual and structural, with three main themes pertaining to peer-led TB ACF: (1) facilitators (2) facilitators for targeted improvement and optimization and (3) barriers. A critical facilitator was the acceptability of peer PWUD in providing TB ACF services. Key facilitators for targeted improvement and optimization included the TB screening tool, mobile TB diagnostic services, integrated methadone/TB services, and monetary incentives to peer PWUD. Barriers included inadequate adherence to infection prevention and control (IPC) measures when providing TB ACF services resulting in a reluctance to wear face masks due to stigma, misconceptions that prior TB preventive therapy among peers negates their need for continued IPC adherence, high mobility of PWUD and the fear of withdrawal symptoms associated with the use of anti-TB medication. Due to this fear, many PWUD preferred not to take anti-TB, as they were concerned about the potential severity of withdrawal symptoms. Conclusion: Our findings highlight the crucial role of peer-led approaches in enhancing TB ACF among PWUD. Peer acceptance as service providers highlights the potential of community-driven interventions. Strengthening facilitators and addressing challenges is key to optimizing these services. Future research should explore the feasibility of providing peer-supported TB diagnosis and treatment services at friendly drop-in centers. Recommendations: 1. Strengthen mobile diagnostic services by increasing their frequency and coverage, enabling timely diagnosis and treatment. 2. Enhance the TB symptom screening tool by including a symptom-independent test, such as a chest X-ray, as the symptoms of illicit drug use can mask and mimic TB symptoms making diagnosis challenging. 3. Address stigma and misconceptions through peer-led education and awareness campaigns that utilize audio-visual materials tailored to PWUD. This will promote adherence to IPC measures and create a more supportive environment for TB ACF activities. 4. Use anti-TB with minimal interactions with opiates or shorter TB treatment regimens to prevent withdrawal symptoms and improve adherence.